Isotopic labelling studies for a gold-catalysed skeletal rearrangement of alkynyl aziridines - Davies, Paul W.; Martin, Nicolas; Spencer, Neil (Beilstein Journal of Organic Chemistry, 2011)
Isotopic labelling studies were performed to probe a proposed 1,2-aryl shift in the gold-catalysed cycloisomerisation of alkynyl aziridines into 2,4-disubstituted pyrroles. Two isotopomers of the expected skeletal rearrangement product were identified using 13C-labelling and led to a revised mechanism featuring two distinct skeletal rearrangements. The mechanistic proposal has been rationalised against the reaction of a range of 13C- and deuterium-labelled substrates.
Keywords: 1,2-aryl shift; cycloisomerisation; gold; isotopic labelling; pyrrole; skeletal rearrangement